Morphological evolution and spatial profile changes of poleward moving auroral forms - A. Goertz; N. Partamies; D. Whiter; L. Baddeley (Annales Geophysicae, 2023)
We investigated the morphology of poleward moving auroral forms (PMAFs) qualitatively by visual inspection of all-sky camera (ASC) images and quantitatively using the arciness index. The PMAFs in this study were initially identified with a meridian scanning photometer (MSP) located at the Kjell Henriksen Observatory (KHO), Svalbard, and analyzed using ASC images taken by cameras at the KHO and in Ny-Ålesund, Svalbard. We present a detailed six-step evolution of PMAF morphology in two dimensions. This evolution includes (1) an equatorward expansion of the auroral oval and an intensification of auroral brightness at the open–closed boundary (OCB), (2) the appearance of an arc-like structure in the oval, (3) poleward and possible west/eastward propagation, (4) azimuthal expansion events, (5) re-brightening of the PMAF and eventual (6) fading away. This is the first work dedicated to the morphological evolution of PMAFs and it includes more detailed discussion and novel aspects, such as the observation of initial merging of 557.7 nm auroral patches to form a PMAF. Moreover, the morphology of PMAFs is quantified using the arciness index, which is a number describing how arc-like auroral forms appear in ASC images. This allows an unbiased statistical investigation of auroral morphology. We present the results of a superposed epoch analysis of arciness in relation to PMAF occurrence. This analysis uncovered that arciness increases suddenly during the onset of a PMAF event and decreases over the PMAF lifetime to return to its baseline value once the event has concluded. This behavior may be understood based on changes in the morphology of PMAFs and validates our understanding of PMAF morphology. Furthermore, our findings relating to arciness may enable automatic identification of PMAFs, which has been found to be notoriously difficult.